Ciudadanías para la Democracia Reflexiones desde la problemática constitucional y constituyente chilena del siglo XXI - Grez, Sergio; Opazo, Daniel (Ariadna Ediciones, 2018)
History and debate on the Chilean institutional system, its characteristics and challenges in the current circumstances